Ethnic entrepreneurship and self-employment in a look at immigrant communities - Gomes, Laura Aparecida Santos (2020)
This article aims to reflect the concept of ethnic entrepreneurship, when it manifests itself in the face of challenges faced by newly arrived immigrant populations, as a condition of self-employment. For this, a theoretical framework was raised to approach the concepts of the entrepreneur, their conceptions, motivations, and necessary personal attributes, as well as the motivations of need and opportunity that awaken the entrepreneurial activity. The concepts of ethnicity, ethnicity, and identity formation were also addressed, as an important factor in the entrepreneurial actions of immigrants. Subsequently, more in-depth researches in immigrant communities are suggested to identify characteristics that influence entrepreneurial activity, whether by necessity in situations of vulnerability or by opportunity.